Application of number theory methods for task solution of intertemporal balance in economy - Zhykhareva, Y.I. (Економічний вісник Донбасу, 2010)
Economic model is presented in which two agents are taking place, which are producer-company and owner-user. They are aggregated presenting productive and non-productive economic fields. Mission is to learn a principal of exploitations availability of intertemporal balance for explanations of change processes in economics. The problem was fully solved at any initial conditions. Key words: agent, property asset, intertemporal balance, balance income, profitableness.